Faktor-Faktor Yang Mempengaruhi Hasil Belajar Mahasiswa Dalam Mata Kuliah Bidang Akuntansi - Apridasari, Esty (Jurnal Dewantara, 2016)
The development of human resources is important in this globalization era, which one of human resource development is in the education sector. The phenomenon shows that the ability of students in understanding the subject in accounting is not really good. This research focuses on the factors that affect student learning outcomes in accounting. This research is descriptive research. Data collection techniques uses questionnaires and documentation. The subjects in this study are students of Islamic Economy of Islamic State Collage (STAIN) Jurai Siwo Metro 2015/2016. Data analysis technique is analyzed by percentage and descriptive. The result of this research indicate that the factors that influence student learning outcomes in accounting are student’s interest and likes, educational background, learning quality which include the way of delivering the subject by the lecturer, the facility and learning media, and the learning time.